Electronic tattoos for health tracking based on graphene oxide; Высокие технологии в современной науке и технике (ВТСНТ-2017) - Lipovka A. A. Anna Anatolyevna; Murastov G. V. Gennadiy Viktorovich; Nozdrina O. V. Olga Vladimirovna; Sheremet E. S. Evgeniya Sergeevna; Kanoun O.; Al-Hamry A.; Prakash V.; Mehta S.; Rodriguez R. D. Raul (Оптические технологии, 2017)
Заглавие с титульного экрана